Development of Student Worksheets Assisted by Grattage Techniques in the Context of Local Culture in Mathematics Learning at State Madrasah Tsanawiyah 5 in Jambi City - Yolanda Ardela; Sunarto Sunarto; Elis Muslimah Nuraida (Journal of Curriculum and Pedagogic Studies (JCPS), 2025)
This study aims to determine the validity, practicality, and effectiveness of teaching materials in the form of student worksheets assisted by grattage techniques in the context of local culture using bar chart material. This study uses a research and development (R&D) approach with the ADDIE development model, which includes the stages of analysis, design, development, implementation, and evaluation. Data collection techniques in this study include documentation, questionnaires, observation, and interviews. The validity test results obtained 96.7% for the “very valid” category of material, 96% for the “very valid” category of language, and 98.1% for the “very valid” category of media. The practicality test results were 96.7% in the “very practical” category by educators, 89.7% in the “very practical” category by small group students, and 84.3% in the “very practical” category by large class students. The results of the effectiveness test showed that all students in the small group achieved the Minimum Passing Grade (MPG) of 6 people, while in the large class, 14 people (70%) achieved the MPG and 6 people (30%) did not achieve the MPG. The results of the effectiveness questionnaire for small group students obtained 89.4% and large group students obtained 83.3% in the “very effective” category. It can be concluded that these mathematics worksheets are valid, practical, and effective for use in mathematics learning. Anggraena, Y., Sufyadi, S., Maisura, R., Chodidjah, I., Takwin, B., Cahyadi, S., et al. (2020). Kajian Pengembangan Profil Pelajar Pancasila. Jakarta: Badan Penelitian dan Pengembangan dan Perbukuan Kementerian Pendidikan dan Kebudayaan Republik Indonesia. Ayurachmawati, P., Asmara, R., & Nopriyanti, T. D. (2024). Pengaruh Pendekatan STEM (Science, Technology, Engineering, Mathematics) Terhadap Kemampuan Berpikir Kritis Kelas V SD Negeri 01 Rasuan. Indonesian Research Journal on Education, 4, 380384. https://irje.org/index.php/irje Leksono, S. (2013). Penelitian Kualitatif Ilmu Ekonomi. Jakarta: RajaGrafindo Persada. Mardia, A., Zulkardi., Putri, R. I. I., & Susanti, E. (2023). Pengembangan LKPD Berbasis PMRI dalam Konteks Piring Makan Ideal pada Materi Pecahan. Transformasi : Jurnal Pendidikan Matematika dan Matematika, 6(2), 155165. https://doi.org/10.36526/tr.v6i2.2365 Mendikbudristek RI. (2024). Peraturan Menteri Pendidikan, Kebudayaan, Riset, dan Teknologi Republik Indonesia, No. 12. Novferma., Syafmen, W., & Wati, I. (2021). Pengembangan LKPD Berilustrasi Komik dengan Konteks Budaya Jambi untuk Meningkatkan Motivasi Belajar Siswa SMP Kelas VII. Focus ACTion Of Research Mathematic, 4(1), 105124. https://doi.org/10.30762/factor-m.v4i1.3261 Riduwan. (2016). Dasar-Dasar Statistika. Bandung: Alfabeta. Subagiyo, P. Y. (1988). Mengenal Lukisan dan Perawatannya. https://www.geocities.ws/primastoria/artikel1/konlukisan1.pdf Sugiyono. (2011). Metode Penelitian Kuantitatif Kualitatif dan R&D. Bandung: Alfabeta. Sulistyawati, W., Wahyudi, W., & Trinuryono, S. (2022). Analisis (Deskriptif Kuantitatif) Motivasi Belajar Siswa dengan Model Pembelajaran Blended Learning di Masa Pandemi Covid19. KADIKMA: Jurnal Matematika dan Pendidikan Matematika, 13(1), 68. https://doi.org/10.19184/kdma.v13i1.31327 Waruwu, M. (2024). Metode Penelitian dan Pengembangan (R&D): Konsep, Jenis, Tahapan dan Kelebihan. Jurnal Ilmiah Profesi Pendidikan, 9(2), 12201230. https://doi.org/10.29303/jipp.v9i2.2141